Literary Translation and Interculturality - Radetič, Andreja (International Journal of English Literature and Social Sciences (IJELS), 2019)
The article attempts to discuss translators’ issues while transferring a source text into a foreign language and culture. The result of this clash, i.e. interculturality, is discussed. The translator’s strategies, such as domestification and foreignizing, and necessary choices, which have to be made to achieve these strategies, e.g. glossing, commenting, writing forewords, are analyzed.